Microwave-Assisted Sol–Gel Preparation of the Nanostructured Magnetic System for Solid-Phase Synthesis - Daniela Istrati; Alina Moroșan; Raluca Stan; Bogdan Ștefan Vasile; Gabriel Vasilievici; Ovidiu Oprea; Georgiana Dolete; Bogdan Purcăreanu; Dan Eduard Mihaiescu (Nanomaterials, 2021)
This work describes a new synthesis method for core–shell magnetite nanoparticles with a secondary silica shell, functionalized with a linker system (Fe3O4-PABA-SiO2-linker) using a microwave-assisted heating technique. The functionalized solid nanomaterial was used for the nanophase synthesis of peptides (Fmoc route) as a solid support. The co-precipitation method was selected to obtain magnetite nanoparticles and sol–gel technique for silica coating using a microwave-assisted (MW) procedure. The magnetic properties of the nanoparticle core offer the advantage of a quick and easy alternative for the magnetic separation of the product from the reaction mixture, facilitating all the intermediary washing and separation operations. The intermediate and final materials were analyzed by advanced characterization methods. The effectiveness of the nanophase peptide synthesis using this nanostructured material as solid support was demonstrated for a short peptide sequence.